Fabrication of Composite Membrane by Constructing Helical Carbon Nanotubes in Ceramic Support Channels for Efficient Emulsion Separation - Kai Yuan; Rizhi Chen; Yiqing Zeng (Membranes)
Membrane technology has emerged as an effective solution for the purification of oily wastewater, particularly in the separation of oil-in-water (O/W) emulsions. However, challenges, such as membrane fouling and the development of robust ceramic membranes with superior stability, continue to limit their widespread application. In this work, helical carbon nanotubes (HCNTs) with interlocking structures were grown in ceramic support channels through the airflow-induced chemical vapor deposition (CVD) method to fabricate membrane material with high hydrophilicity and underwater oleophobicity. The influence of CVD parameters on the growth of HCNTs and the membrane separation performance for O/W emulsions were studied systematically. The optimal HCNTs-SiC composite membrane was prepared at 600 °C, featuring a pore size of 0.95 μm and flux of 229.29 L·m−2·h−1. This membrane demonstrated exceptional purification efficiency (99.99%) for a 500 ppm O/W emulsion, along with a stable flux of 32.48 L·m−2·h−1 under a transmembrane pressure (TMP) of 1.5 bar. Furthermore, the unique membrane structure and surface heterogeneity contributed to its long service life and excellent recovery capability. This work provides a novel strategy for designing high-performance ceramic membranes for oil–water separation, offering potential solutions to current limitations in membrane technology.